Small Peptides Derived from Penetratin as Antibacterial Agents. Issue 4 (11th March 2016) - Parravicini, Oscar; Somlai, Csaba; Andujar, Sebastián A.; Garro, Adriana D.; Lima, Beatriz; Tapia, Alejandro; Feresin, Gabriela; Perczel, Andras; Tóth, Gabor; Cascales, Javier López; Rodríguez, Ana M.; Enriz, Ricardo D.
Abstract : The synthesis, in vitro evaluation and conformational study of several small‐size peptides acting as antibacterial agents are reported. Among the compounds evaluated, the peptides Arg‐Gln‐Ile‐Lys‐Ile‐Trp‐Arg‐Arg‐Met‐Lys‐Trp‐Lys‐Lys‐NH2, Arg‐Gln‐Ile‐Lys‐Ile‐Arg‐Arg‐Met‐Lys‐Trp‐Arg‐NH2, and Arg‐Gln‐Ile‐Trp‐Trp‐Trp‐Trp‐Gln‐Arg‐NH2 exhibited significant antibacterial activity. These were found to be very active antibacterial compounds, considering their small molecular size. In order to better understand the antibacterial activity obtained for these peptides, an exhaustive conformational analysis was performed, using both theoretical calculations and experimental measurements. Molecular dynamics simulations using two different media (water and trifluoroethanol/water) were employed. The results of these theoretical calculations were corroborated by experimental circular dichroism measurements. A brief discussion on the possible mechanism of action of these peptides at molecular level is also presented. Some of the peptides reported here constitute very interesting structures to be used as starting compounds for the design of new small‐size peptides possessing antibacterial activity. Abstract : Peptides derived from penetratin were synthesized and evaluated in vitro for their activity as antibacterial agents. Conformational studies were performed by theoretical calculations and experimental measurements. The peptides RQIKIWRRMKWKK‐NH2, RQIKIRRMKWR‐NH2, and RQIWWWWQR‐NH2 exhibited the strongest antibacterial effects against the Gram‐negative and Gram‐positive bacteria tested in this study.